Increased social deprivation index scores are associated with 180-day readmissions, but not index admissions, for acute heart failure - Robert R. Ehrman; Brian D. Haber; Nicholas E. Harrison; Steven J. Korzeniewski; Lindsay Maguire; Samantha D. Bauer; Phillip D. Levy (PLoS ONE, 2025)
Purpose Hospital readmissions are a pervasive problem for patients with heart failure. While Social Determinants of Health (SDoH) influence many aspects of care, the relationship between readmissions for acute heart failure (AHF) and social vulnerability is incompletely characterized. Such data are needed to develop interventions to maximize successful stabilization in the post-discharge phase. Methods Retrospective review of administrative clinical data paired with ZIP code-level SDoH data from an integrated health system in Detroit, MI. We explored the relationship between Social Deprivation Index (SDI; greater scores indicate more deprivation) and hospital admissions for AHF within 180-days of a prior AHF admission using zero-hurdle regression (logistic model for >0 readmissions; negative binomial model for count of readmissions). Mixed-effects logistic regression, accounting for repeat visits, was used to determine if SDI was associated with AHF-admission for any given ED visit. Results From January 2022 through December 2023, with data from 2,333 unique patients (accounting for 3,281 total visits), we found that each SD increase in SDI (30.6) was associated with increased likelihood of at least one 180day-readmission (OR 1.52 [CI 1.10–2.11]). In the count model, each SD (28.3) increase in SDI was positively associated with 180day-readmissions (relative risk (RR) 1.57 [CI 1.10–1.23]). In the mixed model, after adjusting for characteristics of prior visits, SDI was not associated with AHF admission (including at Index visits). Conclusion These results indicate that area-level social vulnerability may play a role in recovery and stabilization after a decompensation event; it may also extend the post-discharge vulnerable phase. That SDI was not associated with Index AHF admission suggests that social factors may play a different role in development of acute decompensation, as opposed to recovery from it. Development of targeted admission-reduction interventions should consider the varied influences of social vulnerability in the AHF lifecycle.